2014
DOI: 10.1177/0218492314547543
|View full text |Cite
|
Sign up to set email alerts
|

High-quality 3-dimensional imaging for patients with anomalous pulmonary veins

Abstract: The branching pattern of pulmonary veins exhibits many variations. Here we describe 2 patients with lung malignancies who were found to have pulmonary vein anomalies. We performed video-assisted thoracoscopic lobectomies based on preoperative simulations by 3-dimensional computed tomography. Using 3-dimensional computed tomography, a surgeon can easily construct digital images of the patient's pulmonary vessels within a few minutes. Simulation using 3-dimensional computed tomography imaging is useful for furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The recent development of Synapse Vincent raises the question of whether it can yield comparable results in terms of speed and precision. Our previous study demonstrated that preoperative simulation using Synapse Vincent for the assessment of pulmonary vessel branching patterns appear to be beneficial for the safe and efficient performance of VATS anatomical resection and for further understanding of the surgical anatomy related to general thoracic surgery (1)(2)(3)(4). It is safer, more precise, and less invasive for the patient.…”
Section: A B C Dmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent development of Synapse Vincent raises the question of whether it can yield comparable results in terms of speed and precision. Our previous study demonstrated that preoperative simulation using Synapse Vincent for the assessment of pulmonary vessel branching patterns appear to be beneficial for the safe and efficient performance of VATS anatomical resection and for further understanding of the surgical anatomy related to general thoracic surgery (1)(2)(3)(4). It is safer, more precise, and less invasive for the patient.…”
Section: A B C Dmentioning
confidence: 99%
“…The usefulness of a high-speed 3-dimensional (3D) image analysis system, Synapse Vincent (Fuji Photo Film Co., Ltd., Tokyo, Japan) has been reported previously to determine the preoperative simulation of lung segmentectomy and video-assisted thoracic surgery (VATS) (1)(2)(3)(4), as well as the best positioning of robot assisted thoracic surgery (5). An overview of these studies shows the effectiveness of preoperative simulation and intraoperative…”
Section: Introductionmentioning
confidence: 99%